OPTIMALISASI PROSES FERMENTASI URIN SAPI MENJADI BIOURIN - Merisa Aritonang; Yohanes Setiyo; Ida Bagus Putu Gunadnya (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2013)
An experiment on biourine fermentation using cow urine has been carried out. The objective of this research was to optimize biourine fermentation by adding starter and palm sugar. The reseach used Completed Randomized Block Design with factorial pattern of 2 factors and 3 levels each. The first factor was starter concentrations of Rumino bacillus 0, 15, and 30 ml. The second one was weight of palm sugar added at 0, 15, and 30 g. Each treatment was repeated 3 times. Varibles observed were pH, acid, soluble solid, organic C, and total N. Results of the research indicated that starter addition of 15-30 ml and palm sugar 15 - 30 g for every 1500 ml cow urine accelerated biourine production in the fermentation stage of cow urine which was taken from simantri number 225. The fermentation process was carried out for 7 days and by adding this combination of traitment shortening the process to 5 days. This was shown by pH,total acid,and total dissolve solids value of urin which was stable after 5 days of fermentation. Concentration of 30 ml R. bacillus with the addition of 30 grams brown sugar in 1,500 ml of fermented cow urine is the optimal treatment in which the value of pH is 6, 0.5% total acid, and 3.80Brix total dissolved solids. This is supported by the standard of Permentan Number 70 with a pH value of 4-9. However, the research for C-organic and N-total has not fulfilled the standard of Permentan in which the C-organic is 6% and N total is 3-6%.